Interfacial Coordination Induced Crystalline Metallacyclic Membrane for High‐Performance Enantioseparation - Run‐Hao Li; Yumei Wang; Yi Liu; Yue Sun (Aggregate)
ABSTRACT Membranes offer an attractive route to efficient enantioseparation, especially compared with energy‐intensive techniques like chromatography. However, tuning membrane structure and porosity to separate chiral molecules remains challenging. Here, we present a process for producing intrinsically chiral, ordered discrete metallacycycle 1 membranes on polyacrylonitrile supports through interfacial coordination‐driven self‐assembly using organic precursor 2 and metallic precursor 3. These chiral membranes, with their orientated architecture, exhibit ultra‐high enantioselectivity (up to 100%) and permeation efficiency for racemic 1‐phenylethanol, 1‐phenylethylamine, and 2‐phenylglycinol. Thermodynamic data and molecular simulations revealed the retarded transport mechanism of the membrane, resulting in highly efficient enantioseparation. Notably, when integrated into a circuit‐controlled 3D‐printed module, the aligned metallacyclic membrane retained its enantioselectivity for high‐value pharmaceutical racemic salbutamol. This approach provides a feasible strategy for creating supramolecular metallacyclic channels in chiral membranes, demonstrating the potential for accurate enantioseparations.